Recent advances in imaging in management of symptomatic internal carotid artery disease - Szabo, Kristina; Kern, Rolf; Hennerici, Michael G. (International journal of stroke, 2007)
The management of patients with internal carotid artery stenosis needs to focus on the occurrence and identification of neurological symptoms, the degree and morphology of the stenosis and the determination of the mechanism of cerebral ischemia. Thus neuroimaging studies are an integral part of the neurologist's assessment of these patient and individual therapeutic decisions. Since a differentiated approach is not always taken and patients by far too often undergo surgical or interventional treatment without a proper neurological evaluation, the material presented in this review demonstrates the possibilities of such a critical assessment concerning brain and vascular imaging findings and new techniques as well as modern concepts of plaque vulnerability improving the understanding of the pathophysiology and mechanisms of ischemic symptoms in internal carotid artery disease. Furthermore, the results of recent clinical trails that need to be integrated in the optimal treatment plan of these patients are discussed.